Ponzi schemes and the financial sector : DMG and DRFE in Colombia (2017)
By the time the Colombian government closed DMG and DRFE, two Ponzi schemes that were operating in Colombia until 2008, over half a million customers had deposited funds corresponding to 1.2% of Colombia's annual GDP. We show that the individuals who invested in DMG and DRFE obtained close to 40% more loans in the formal financial sector prior to the government closing these firms, compared to similar individuals who did not invest in these pyramids. Moreover, deposits in the formal financial sector fell in those municipalities affected by these two pyramids: a one-standard deviation increase in the municipal presence of the pyramid schemes reduced municipal saving deposits by 2.9% and Certificate Deposits by close to 10%. After the firms were shut down, the proportion of nonperforming loans of investors rose 35% above non-investors¿ loans; two years later, investors¿ deposits had not yet fully recovered.